American sports fiction - Cocchiarale, Michael, 1966-; Emmert, Scott, 1962- (Ipswich, Massachusetts : Salem Press, 2013)
"Experts in the field of sports literature, editors Michael Cocchiarale and Scott D. Emmert, Associate Professors of English at Widener University and the University of Wisconsin-Fox Valley, respectively, present a collection that analyzes works by many of the most well known authors of the last century, including Ernest Hemingway, Jack London, Don Delillo, and David Foster Wallace. Introductory chapters offer a survey of critical approaches as well as history of the genre that will be instructive for students and their teachers, drawing the dimensions of the field within which writers and scholars consider sports and fiction. After these contextualizing essays come nine chapters that take particular critical views of selected works of both canonical and understudied sports fiction, providing original readings that keep both teacher and student in mind. Why this literature is important and how readers can more fully understand it guide the selections for a volume distinguished in its scope and originality. Contributors include Peter Kratzke, Tracy J.R. Collins, Scott D. Peterson, and Mathew J. Bartkowiak."--Easons.com.
On American sports fiction / Michael Cocchiarale and Scott D. Emmert -- Critical contexts : Logos, nostos, eros, thanatos: Don DeLillo's "Pafko at the Wall" and end zone from a narratological perspective / Mark S. Graybill ; The history and cultural influence of sports fiction in America / Tracy J.R. Collins ; On a higher level: transcendence and purity in the literature of sports / Matthew J. Bartkowiak ; American sports fiction: a critical review / Susan J. Bandy -- Critical readings : More than "clever journalists": the cultural contributions of Noah Brooks, Ring Lardner, and Heywood Brown to American sports fiction / Scott D. Peterson ; After touring, the return to "real life": Frank Stockton's A Bicycle of Cathay / Peter Kratzke ; Fact, fantasy, and fan appreciation in Eric Rolfe Greenberg's The Celebrant / Eric Sterling ; Would Karl Marx call for an overthrow of ESPN? Sports as an opiate of the people / Greg Ahrenhoerster ; Don't apologize: class, masculinity, and the promise of ascent in Fat City and The Game / Mark Dziak ; Bambara's "Raymond's run": Hazel Parker as trackster and trickster / Mary Comfort ; John L. Parker Jr.'s Once a Runner and the Daimonic mindscape of sport / James Pipkin ; David Foster Wallace and the athlete's war with the self / Matthew J. Darling ; "Somewhere in this favored land": muscle and magic in the sports fictions of Michael Chabon / Joseph Dewey.
Includes bibliographical references (pages 259-260) and index.
Keywords: American fiction -- History and criticism; Sports in literature; Sports stories, American -- History and criticism; Athletics in literature